STRATEGI PEMASARAN PENJAHIT PAKAIAN DI MASA PANDEMI COVID-19 MELALUI PENGEMBANGAN KEGIATAN EKONOMI KREATIF - Amelia, Zaida; Malihah, Lola (Journal MISSY (Management and Business Strategy), 2022)
This research aims to find out the strategy carried out by one of the Small and Medium Enterprises (MSMEs) in increasing income during the Covid-19 pandemic, by developing the creative economy. This research is field research with a qualitative approach, by conducting a discussion to the research subject and reviewing various related theories as reference materials. Various efforts were carried out by MSME actors in increasing income during the pandemic. Of course, innovation and creativity are needed, in order to bring up something new that is considered interesting. With this strategy, it can help business actors in developing their business. In today's digital era, it can be used to make it easier to promote a product either through social media such as WhatsApp, Facebook, or others.